Observation of large electrocaloric properties in lead-free Ba0.98Ca0.02Ti0.98Sn0.02O3 ceramics - Ramovatar; Indrani Coondoo; Pradip Kumar; Azam A. Khan; S. Satapathy; Neeraj Panwar (AIP Advances, 2019)
Tetragonal lead-free Ba0.98Ca0.02Ti0.98Sn0.02O3 (BCST) compound sintered at 1400 °C was investigated for its electrocaloric properties. The large adiabatic temperature variation, ΔT ∼ 0.476 K and isothermal entropy change, ΔS ∼ 1.90 J/kg.K were obtained at ∼ 373 K at an electric field of 20 kV/cm. Further, higher electrocaloric coefficients (ΔT/ΔE ∼ 0.238 K.mm/kV and ΔS/ΔE ∼ 0.952 J.mm/K.kg.kV) with better refrigeration capacity (RC ∼ 152 J/kg) were achieved at the same temperature and electric field. The ΔS/ΔE and RC values for this compound are better than that observed in various other lead-free ferroelectric ceramics.